2015
DOI: 10.1111/vox.12234
|View full text |Cite
|
Sign up to set email alerts
|

Passive reporting greatly underestimates the rate of transfusion‐associated circulatory overload after platelet transfusion

Abstract: Platelet-associated TACO is greatly underestimated by passive reporting in the adult patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 13 publications
2
39
0
1
Order By: Relevance
“…This study, which retrospectively surveyed 4857 transfusion episodes of adult inpatients aged >18 years over a 6‐month period at four academic tertiary care hospitals in the United States, found that serious cardiopulmonary transfusion reactions occurred in approximately 1% of all transfusion episodes. TACO was the most common reaction noted in this study, consistent with the relatively high incidence rates reported by active surveillance studies . The incidence of other serious transfusion reactions was difficult to accurately estimate due to their low levels of apparent occurrence, which was not unexpected given our moderate sample size.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This study, which retrospectively surveyed 4857 transfusion episodes of adult inpatients aged >18 years over a 6‐month period at four academic tertiary care hospitals in the United States, found that serious cardiopulmonary transfusion reactions occurred in approximately 1% of all transfusion episodes. TACO was the most common reaction noted in this study, consistent with the relatively high incidence rates reported by active surveillance studies . The incidence of other serious transfusion reactions was difficult to accurately estimate due to their low levels of apparent occurrence, which was not unexpected given our moderate sample size.…”
Section: Discussionsupporting
confidence: 73%
“…Although 27 of 43 (63%) adjudicated TACO or TRALI/possible TRALI cases had documentation in clinical notes suggesting the possibility that a transfusion was associated with cardiopulmonary symptoms, only three reactions (two TACO, one TRALI/possible TRALI) were reported to the transfusion medicine service/hospital blood bank. Under‐reporting of transfusion reactions has been described in prior studies, and one study found that only 14% of TRALI/possible TRALI cases and 11% of TACO cases were reported to the transfusion service . A better understanding of why cardiopulmonary transfusion reactions are less likely to be reported to the transfusion service than febrile or allergic reactions is an important step in improving such reporting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report on transfusion-associated circulatory overload showed considerable underreporting, with a 36-fold difference in detection between active and passive surveillance: 1:5997 cases reported by passive surveillance vs 1:167 by active surveillance. 21 Furthermore, there is considerable variation in the reported incidence of transfusion reactions to platelets, with recent reports ranging from 0.01% to 10.0%, with considerable variation in reaction severity definitions and surveillance methods likely accounting for this wide range. [22][23][24] Platelet components are particularly vulnerable to bacterial contamination, mainly due to their storage at room temperature, which allows growth of small inocula to very high titers and limits the shelflife of these products.…”
Section: Discussionmentioning
confidence: 99%
“…While national haemovigilance systems are valuable and contribute to our understanding of transfusion reactions, a significant limitation is that reactions are captured by a passive reporting system, thereby underestimating true incidence . Active surveillance for severe transfusion reactions may offer a more accurate assessment of the incidence and characterization of severe transfusion‐related acute adverse events and provide insight on how to refine haemovigilance criteria to be more sensitive and specific .…”
Section: Introductionmentioning
confidence: 99%